The Effect of E-Learning on Lifestyle in Adolescents with Thalassemia Major - Poorhosein Fookolaee, Sakineh; Talebishelimaki, Somayyeh; Tahmasebi, Homyra; Arab, Masoume; Akbarnatajbishe, Kolsoum; Darvish-Khezri, Hadi; Kosaryan, Mehrnoush (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: One of the ways to improve the quality of life of patients with thalassemia major is to empower patients through education to deal with the effects and complications of illness and control disease and life further. This study aimed to determine the impact of E-learning intervention on self-care behaviors in patients with thalassemia major. Methods: The present study is a quasi-experimental study of clinical trial type. The effect of e-learning on the lifestyle of eligible adolescents with thalassemia major of both sexes referred to Razi, and Bu Ali Sina Hospitals was investigated. Samples were divided into two groups control (N=25) and intervention (N=25). The control group received routine training from the relevant centers or health care staff, and the intervention group received e-learning and regular exercise. Data were collected through valid and reliable questionnaires, including two main parts. The first part contains demographic information. The second part of the questionnaire was a standard health-promoting behaviors questionnaire that assesses the lifestyle of adolescents in three dimensions nutrition, physical activity, and stress management. Finally, data were analyzed using SPSS version 22, and P-value less than 0/05 was considered significant. Results: Obtained results demonstrated a significant difference in the quality of nutrition in adolescents with thalassemia before e-learning intervention between intervention and control groups (P< 0.05). Moreover, after the intervention, there was a significant difference in the stress management of the intervention and control groups, and the scores of the intervention group increased significantly (P< 0.05). The findings also indicated that physical health was also considerably increased in adolescents with thalassemia after intervention by e-learning compared to the control group (P< 0.05). Conclusions: It can be concluded that e-learning has a significant effect on patients' quality of life with thalassemia in three dimensions: nutrition, physical and mental health. The results of this study can serve as a guideline for designing appropriate educational programs for thalassemia patients.